2023
DOI: 10.1093/gbe/evad164
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of an Alternative Genetic Code in the Providencia Symbiont of the Hematophagous Leech Haementeria acuecueyetzin

Alejandro Manzano-Marín,
Sebastian Kvist,
Alejandro Oceguera-Figueroa

Abstract: Strict blood-feeding animals are confronted with a strong B-vitamin deficiency. Blood-feeding leeches from the Glossiphoniidae family, similarly to hematophagous insects, have evolved specialized organs called bacteriomes to harbor symbiotic bacteria. Leeches of the Haementeria genus have two pairs of globular bacteriomes attached to the esophagus which house intracellular “Candidatus Providencia siddallii” bacteria. Previous work analyzing a draft genome of the Providencia symbiont of the Mexican leech Haemen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 69 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…The one notable exception is the absence of nudB . However, the nudB gene is not universally conserved across endosymbionts of blood-feeding organisms ( 27 , 28 , 57 ). In fact, it has been shown that many phosphatases display wide-range substrate specificities in Escherichia coli ( 65 , 66 ), suggesting that other phosphatase(s) encoded in the symbiont’s genome might be fulfilling a similar role to nudB .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The one notable exception is the absence of nudB . However, the nudB gene is not universally conserved across endosymbionts of blood-feeding organisms ( 27 , 28 , 57 ). In fact, it has been shown that many phosphatases display wide-range substrate specificities in Escherichia coli ( 65 , 66 ), suggesting that other phosphatase(s) encoded in the symbiont’s genome might be fulfilling a similar role to nudB .…”
Section: Resultsmentioning
confidence: 99%
“…These bacteriomes harbor the gammaproteobacterial symbiont ‘Candidatus Providencia siddallii‘ (hereafter Pr. siddallii ), which has been shown to hold small A+T-biased genome-preserving complete pathways for B vitamin biosynthesis ( 28 ). These characteristics, along with congruence between the phylogenetic relations among the leech hosts and symbionts, support the obligate and “ancient” nature of Pr.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the novel symbiont retains redundant enzymes for some metabolic steps of the B vitamin biosynthetic pathways, unlike Pr. siddallii and other well established symbionts (Bennett and Moran, 2015; Koga and Moran, 2014; Manzano-Marín and Latorre, 2016; Manzano-Marín et al ., 2023b). These metabolic features all support a younger age for the association of Haementeria leeches with Pluralibacter compared to that with Provdencia .…”
Section: Resultsmentioning
confidence: 99%
“…The one notable exception is the absence of nudB. However, the nudB gene is not universally conserved across endosymbionts of blood-feeding organisms (Manzano-Marín et al, 2015, 2023bŘíhová et al, 2023). In fact, it has been shown that many phosphatases display a wide-range substrate specificities in Escherichia coli (Haase et al, 2013;Kuznetsova et al, 2006), suggesting other phosphatase(s) encoded in the symbiont's genome might be fulfilling a similar role to nudB.…”
Section: /14mentioning
confidence: 99%
See 1 more Smart Citation